1999
DOI: 10.1017/s0007123499000125
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Theory of Rational Nominating Behaviour Applied to Japanese District Elections

Abstract: Plurality electoral systems with multi-member districts and single nontransferable votes (SNTV) allow parties to win multiple seats in district elections by nominating multiple candidates, but they also penalize a party's seat share if the number of candidates offered is 'too many' or 'too few'. Given an institutional incentive to nominate the 'correct' number of candidates, we seek to establish empirically that the nominating behaviour of parties in such systems results from a rational calculus of strategic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 0 publications
0
29
0
Order By: Relevance
“…Under SNTV, much of the intraparty competition takes place in the general election stage, as parties routinely nominate multiple candidates in the same district. While the optimal strategy is for a party to nominate the "right" number of candidates and then distribute its support evenly among them Cox and Thies 1998;Browne and Patterson 1999), overnomination is not always a disaster. If more than the appropriate number of candidates insists on running and no compromise can be found, the party can sometimes simply let them all run and let the electorate decide which is the weakest.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Under SNTV, much of the intraparty competition takes place in the general election stage, as parties routinely nominate multiple candidates in the same district. While the optimal strategy is for a party to nominate the "right" number of candidates and then distribute its support evenly among them Cox and Thies 1998;Browne and Patterson 1999), overnomination is not always a disaster. If more than the appropriate number of candidates insists on running and no compromise can be found, the party can sometimes simply let them all run and let the electorate decide which is the weakest.…”
Section: Resultsmentioning
confidence: 99%
“…Governing parties have a tremendous advantage because they can use the resources of the state to overcome these coordination problems (Cox 1996Rosenbluth 1993, 1996;Patterson and Stockton 2010;. Many studies have found that a key reason for prolonged periods of LDP dominance was the LDP's ability to accomplish strategic nomination and vote coordination (Browne and Patterson 1999;Horiuchi and Kohno 2004). 4 If governing parties are expected to do well under SNTV, so are small parties.…”
Section: Party Politics Under Sntv In Japan and Taiwanmentioning
confidence: 99%
“…They would then ask if the resulting votes received by KMT4-the best this fourth nominated KMT candidate could do-would be sufficient to defeat the weakest winning candidate, PFP2, who obtained 38,799 votes. Since the fourth nominated KMT candidate receives 41,375 votes under the alternative nomination strategy, and this amount exceeds that obtained by PFP2, Cox and Niou (1994) and Browne and Patterson (1999) would have labeled this an overnomination.…”
Section: Assessing Nomination Strategies Under Sntvmentioning
confidence: 99%
“…Taking the KMT's nomination strategy as an example, we note that both Cox and Niou 1994) and Browne and Patterson (1999) would evaluate it in the same way. Because the KMT nominated five candidates but obtained only three seats, they would evaluate this strategy by asking if there is an alternative the KMT could have employed that would result in it winning an additional seat.…”
Section: Assessing Nomination Strategies Under Sntvmentioning
confidence: 99%
“…The failure to coordinate on an optimal number of candidates results in an inferior outcome. Political parties, for example, can be penalized by loss of seats for nomination errors, including running too many candidates and thus dividing the vote among supporters, or running too few candidates and losing an additional seat (Reed, 1990;Cox and Niou, 1994;Browne and Patterson, 1999).…”
Section: Introductionmentioning
confidence: 99%